The dashboard school: governing teachers, students and parents in the data-driven school. - Zomer, Chris; Pangrazio, Luci; Matovich, Ivan (Discourse: Studies in the Cultural Politics of Education, 2026)
The use of digital data dashboards is increasingly common in education. Dashboards often have visually appealing layouts and promise to make complex phenomena and large data sets visible and actionable to inform so-called 'data-driven' decision-making. In this paper we present a case-study of local dashboard governance in an independent school in Australia that recently implemented a series of dashboards created with Microsoft PowerBI. Drawing on in-depth interviews with school leaders and staff, as well as on screenshots of the dashboards, we argue that the form of dashboard governance imagined and implemented by the school, exacerbates already existing neoliberal practices in education, such as the optimisation of school metrics (mostly through standardised test data), the self-disciplining of teachers through continuous comparisons, and the 'gamesmanship' of accountability vis-à-vis parents. We conclude this paper by arguing that data-driven dashboard governance, recodes existing educational practices, creates new subjectivities, and reshapes relations within the school.